Mucinous Intrapapillary Neoplasm Of The Pancreas. Case Report - Génesis Pauleth Carrillo Velasco; Hernán Patricio Martínez Calderón (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Mucinous intrapapillary neoplasia of the pancreas was first described in 1980. Its incidental diagnosis in routine cross-sectional imaging studies has increased. Branched duct intraductal papillary mucinous neoplasms (BD-IPMN) are the most common cystic lesions encountered in practice and carry a low, but not insignificant, risk of developing cancer in the long term. Most lesions are asymptomatic and benign, but some lesions carry a significant risk of malignant transformation, so proper identification of these lesions is critical.Objective: Develop the case report of a patient with mucinous intrapapillary neoplasia of the pancreas.Methodology: A clinical case of a 51-year-old female who was admitted to the emergency room due to severe abdominal pain is reported, an imaging study was performed in which a mass with a diagnosis suggestive of IPNM was visualized, a splenopancreaticoduodenectomy was performed, which presented complications, for which is converted to laparotomy, a histopathologic diagnosis of IPNM is provided.Conclusions: IPNM is characterized by a mass with an abundant amount of mucinous material, its progression is slow, its diagnosis is usually incidental when performing imaging studies, it presents a cancerous tendency with an average of 5 years, its therapy must be radical surgery to avoid recurrences, which occur in 60-70% of patients with tail and body of residual pancreas.